2011
DOI: 10.1007/s00421-011-2038-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold acclimatization on exercise economy in the cold

Abstract: We sought to determine if cold acclimatized men display higher economy (i.e. lower oxygen consumption at a given workload) during graded cycle ergometry in the cold (5°C). After completing a familiarization trial 1 week prior, five cold weather athletes (CWA) and eight physically active men (NON) underwent graded exercise tests to volitional fatigue in 5°C. The protocol always started at 60 W and increased by 20 W each minute. Oxygen consumption (VO(2)), respiration rate (RR), tidal volume (TV), and respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“…However, cold muscle temperatures did cause an increase in stride frequency and decrease in stride length which were attributed to a change in muscle tendon elasticity. Interestingly, cold acclimatization has been shown to reduce the VO 2 at any given power output during cycle ergometry (167), although the use of independent groups makes a definitive conclusion tentative.…”
Section: Metabolismmentioning
confidence: 98%
“…However, cold muscle temperatures did cause an increase in stride frequency and decrease in stride length which were attributed to a change in muscle tendon elasticity. Interestingly, cold acclimatization has been shown to reduce the VO 2 at any given power output during cycle ergometry (167), although the use of independent groups makes a definitive conclusion tentative.…”
Section: Metabolismmentioning
confidence: 98%
“…Muller et al 87) reported that cold weather athletes, who practiced American football in cold air (0°C on average), showed a greater exercise economy (smaller oxygen uptake for a given submaximal workload) during bicycle exercise in 5°C air compared to a physically active control group. It was speculated, without supporting data, that improved buffering of lactate or utilization of different muscle fiber types could be a mechanism underpinning the greater exercise economy.…”
Section: Enhancement Of Cold Induced Vasodilatationmentioning
confidence: 99%
“…In humans, attenuated metabolic responses associated with cold habituation have been linked to improvements in exercise economy in the cold [i.e. lower oxygen uptake and respiratory exchange ratio (RER)] [ 137 ]. A lower RER is reflective of preferential fat oxidation, which may provide a beneficial cross-adaptation effect at altitude if carbohydrate utilization is spared for exercise performance.…”
Section: Cross-adaptation: Cold Habituation and Altitudementioning
confidence: 99%